Answer:
x = -3
Explanation:
If the equation is correctly written as 15·x = -27 + 6·x
Then we have;
15·x = -27 + 6·x
We subtract 6·x from both sides to have all the variables (x) on one side as follows;
15·x - 6·x= -27 + 6·x - 6·x
Which gives;
x·(15 - 6) = -27 + x·(6 - 6)
We note that 6 - 6 = 0, therefore, we have;
x × 9 = -27 + x × 0
We not that x × 0 = 0, therefore;
x × 9 = -27
We now divide both sides with the 9 to get the value of x alone as follows;
x×9/9 = -27/9
Which gives;
x = -27/9 = -3
x = -3